2012
DOI: 10.1073/pnas.1118566109
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a transposon into a derived prolactin promoter with function during human pregnancy

Abstract: Transposable elements (TEs) are known to provide DNA for host regulatory functions, but the mechanisms underlying the transformation of TEs into cis-regulatory elements are unclear. In humans two TEs-MER20 and MER39-contribute the enhancer/ promoter for decidual prolactin (dPRL), which is dramatically induced during pregnancy. We show that evolution of the strong human dPRL promoter was a multistep process that took millions of years. First, MER39 inserted near MER20 in the primate/rodent ancestor, and then th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 43 publications
5
60
0
Order By: Relevance
“…We also have yet to identify the elements regulating viviparity-associated gene expression; more genomic information will permit evaluation of potential gene expression promoters and the influence of transposable elements on gene expression (e.g. Emera & Wagner (2012) and Jacques et al (2013)). …”
Section: R21mentioning
confidence: 99%
“…We also have yet to identify the elements regulating viviparity-associated gene expression; more genomic information will permit evaluation of potential gene expression promoters and the influence of transposable elements on gene expression (e.g. Emera & Wagner (2012) and Jacques et al (2013)). …”
Section: R21mentioning
confidence: 99%
“…A classic example is the expressed pseudogene, which can arise by gene duplication followed by degeneration of one redundant copy by random accumulation of mutations (Balakirev and Ayala 2003;Zheng et al 2007). Functionless transcripts might also arise from transposon promoters (Emera and Wagner 2012;Hancks and Kazazian 2012). It is also reasonable to assume that transcriptional errors occur at a nonzero rate.…”
mentioning
confidence: 99%
“…In the case of decidual cells, target gene recruitment is, at least in part, mediated through the evolution of alternative promoters and cell type specific enhancers from transposable elements. This was first discovered for the decidual promoter of PRL (Emera et al, 2011a, Emera and Wagner, 2012, Gerlo et al, 2006. The decidual promoter consists of DNA from two transposable elements, MER20 and MER39 (Gerlo et al, 2006).…”
Section: Molecular Mechanisms For the Evolution Of Decidual Cellsmentioning
confidence: 99%
“…The expression of decidual PRL (dPRL) is regulated by an alternative promoter about 6 kb upstream of the first coding exon (Berwaer et al, 1994, Gellersen et al, 1994 that is derived from two transposable elements (Emera et al, 2011a, Emera and Wagner, 2012, Gerlo et al, 2006. A number of transcription factors have been identified that participate in the regulation of dPRL.…”
Section: Molecular Mechanisms For the Evolution Of Decidual Cellsmentioning
confidence: 99%